2022
DOI: 10.14710/ijred.2022.41275
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adding Combustion Air on Emission in a Diesel Dual-Fuel Engine with Crude Palm Oil Biodiesel Compressed Natural Gas Fuels

Abstract: A diesel dual-fuel engine uses two fuels designed to reduce the consumption of fossil fuels. Generally, the specific fuel consumption of diesel dual-fuel engines has increased.  However, in   combination with alternative fuels, namely compressed natural gas injected through air intake, the use of diesel fuel can be reduced. However, using two fuels in a diesel dual-fuel engine increases the equivalent ratio; therefore, the air and fuel mixture becomes richer because the air entering the cylinder during the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Through the reduction of greenhouse gas emissions and the mitigation of waste disposal issues, its production advances the circular economy (Hoang et al, 2022a;Kapoor et al, 2020). Collectively, these biofuels provide a substantial contribution to the creation of renewable energy sources and the lessening of environmental harmful impacts (Nguyen-Thi and Bui, 2023;Yilmaz, 2012;Yuvenda et al, 2022).…”
Section: Application Of Machine Learning In Biofuelsmentioning
confidence: 99%
“…Through the reduction of greenhouse gas emissions and the mitigation of waste disposal issues, its production advances the circular economy (Hoang et al, 2022a;Kapoor et al, 2020). Collectively, these biofuels provide a substantial contribution to the creation of renewable energy sources and the lessening of environmental harmful impacts (Nguyen-Thi and Bui, 2023;Yilmaz, 2012;Yuvenda et al, 2022).…”
Section: Application Of Machine Learning In Biofuelsmentioning
confidence: 99%
“…The energy crisis is the tension that the supply of energy cannot fulfil the high level of demand and divert to renewable energy (Sani et al, 2023). Crude palm oil (CPO) as a renewable energy source is a vegetable oil that has the highest triglyceride content when compared to oils from other plants such as Jatropha curcas (Islam et al, 2017;Yuvenda, Sudarmanta, Wahjudi, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has demonstrated that biodiesel, bioethanol, and biogas are superior to fossil fuels in terms of energy production (Cherwoo et al, 2023;Nguyen et al, 2024;Priya et al, 2022). Biodiesel, which is also known as fatty acid methyl ester, has been utilized as a viable alternative to fossil fuels for a considerable amount of time (Jeyakumar et al, 2023;Raheman and Padhee, 2014;Yuvenda et al, 2022). Many benefits are associated with the use of biodiesel in comparison to diesel and gasoline, in which its biodegradability, high flash point, non-toxicity, and high cetane number are just a few of the features that it possesses regarding its properties (Karthickeyan et al, 2020;Tuan Hoang et al, 2021).…”
mentioning
confidence: 99%